Strategi Manajemen SDM dalam Menekan Turnover intention pada Lawson Aniva Junction PT Lancar Wiguna Sejahtera Kabupaten Tangerang - Lintastik Zagoto; Dodi Prasada (STIE AUB Surakarta, 2026)
This study examines how Human Resource Management (HRM) strategies reduce turnover intention among employees at Lawson Aniva Junction, PT Lancar Wiguna Sejahtera, Tangerang Regency. Unlike previous studies that mainly emphasize factors influencing turnover intention, this research explores the implementation of HRM strategies in a retail convenience store using a qualitative approach. Data were collected from January to March 2026 through semi-structured interviews, observation, and documentation involving five purposively selected informants. The findings indicate that HRM practices remain operationally oriented, while high workloads and inconsistent shift schedules continue to encourage turnover intention. The study highlights the importance of structured HRM strategies to improve employee retention and operational sustainability.